PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN SELADA (Lactuca sativa L.) SECARA ORGANIK DENGAN PENGAPLIKASIAN BERBAGAI DOSIS PUPUK HAYATI CAIR - Aminiati Mulyaningsih Perbawani; Mariyatul Qibtiyah; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
The lettuce plant is one of the vegetables that can be eaten raw, as it has a fairly high mineral content. Fertilization provides a very large role to increase the resulting product. Currently, farmers in Indonesia are beginning to understand the importance of organic fertilizers in the cultivation process. This is based on the knowledge that inorganic fertilizers have a negative impact on the environment if used excessively and in the long term. Biofertilizer is an alternative that utilizes certain microorganisms to provide nutrients and help plant growth. The purpose of the study was to determine the response of growth and production of organic lettuce plants to the dosing of liquid biofertilizer. This study applied the Complete Randomized Design method consisting of one factor with seven levels repeated four times. The factor is the dose of liquid biofertilizer including: 0 l/ha, 100 l/ha, 200 l/ha, 300 l/ha, 400 l/ha, 500 l/ha, and 600 l/ha. The parameters observed were plant height, number of leaves, wet weight per sample plant, wet weight per hectare and root length. Data obtained from the observations were calculated using 5% analysis of variance (ANOVA) method. If there is a real effect, it is further tested with the BNT (Least Real Difference) method at the 5% level. The results stated that the observation of lettuce plant growth, the dose of 100 l/ha gave the best results, while in the harvest the dose of 200 l/ha gave the best results compared to other treatments.